MODELLING OF PACKED COLUMN FOR CO2 ABSORPTION IN ALKANOLAMINES AT HIGH-PRESSURE AND HIGH-CO2 LOADING CONDITIONS - SHAHID, MUHAMMAD ZUBAIR (2021)
The interest of treating natural gas at high pressure and high carbon dioxide (CO2) concentrations has been increasing to exploit CO2 rich natural gas reserves. Chemical absorption using alkanolamines in a packed column has been regarded as the most established CO2 capture technique. In modelling this system, the Pandya’s rate-based model is the most widely implemented approach to simulate the CO2 absorption process using alkanolamine solutions. However, the studies are limited to the conditions of low pressure (≈ 1 atm) and low CO2 loadings (e.g. < 0.5molCO2/molMEA). At the conditions of high pressure and high CO2 loadings, the real CO2 absorption phenomena is more complex which has not been reflected by the model. Nevertheless, a few of the modelling studies had tried to extend the model using correction factors derived from the experimental data.